Agile Software Testing Technologies in a Large Scale Project - Koteska, Bojana; Mishev, Anastas (CEUR Workshop Proceedings (CEUR-WS.org, ISSN 1613-0073), 2012)
Software testing in agile development is very complex issue in the IT world. Since agile methods do not focus much on testing activities and agile software development does not include testing practices required for a quality project, the process of finding the suitable method for testing, especially for large scale projects is challenging. In this paper, we propose a concept of integrated agile software testing in a large scale project. This research explains the software testing process technologies and principles for agile software testing and identifies the best practices for testing software products in agile development process.
Keywords: Agile software testing, large-scale software project, agile software development